Post Covid: Redefine Physical Work Environment in Coworking Space - Nazri, Qayyiem Ahmad; Sharif, Roslina (MAJ - Malaysia Architectural Journal, 2023)
Gig economy has been arising due to covid 19 pandemic hit as people starting to work remotely and high demand on flexible working place. Previous studies highlight on the factors of work environment influencing user satisfaction in coworking space. However, there is a limited study on the physical environment in the coworking space due to current pandemic crisis. Therefore, my study will identify new typology of space planning in coworking space that need to be adapt on current endemic situation to cater helathy working environment in the future. In this research, content analysis will be used as the research inquiry on the characteristic on current coworking space and questionnaires survey will be conduct on the identifying the element that can be improve in designing current coworking space due to endemic situation. Hence, this research will explore on the design guideline on current physical environment in coworking space to fullfill users satisfaction in term of wellbeing and health safety.Contribution and benefits of this study are coworking space can be sustain with healthy environment and support on economic growth. Future research can add more variables to the existing study by integrating entertainment space in coworking space.